Merdeka Mengajar: an Ultimate Platform for Teachers' Competence Development - Fadhil Zil Ikram; Nursyam Anaguna; Rosidah (Jurnal MediaTIK, 2023)
This research is a literature study that aims to explain the usefulness of the features of the Merdeka Mengajar Platform to develop teacher competencies. The data sources of this research were obtained from the Merdeka Mengajar Platform and research articles in journals. The analysis used in this research was content analysis, which began with data making, then continued with abductively inferring contextual phenomena, and ended with narrating the answer to the research question. The government launched the Merdeka Mengajar (PMM) platform to assist teachers in developing their competence. This platform allows teachers to carry out self-development anywhere and anytime. The features owned by PMM can help develop the four competencies teachers have. Personal competence and social competence can be developed in the Community Features and Real Action in Self-Training. Pedagogical competence can be developed through the curriculum introduction feature, student assessment, teaching tools, self-training, inspirational videos, and proof of work. Finally, professional competence can be developed through student assessment, teaching tools, and self-training features.